Sudden cardiac death in patients with nonischemic cardiomyopathy - Betensky, Brian P. (Indian Heart J, 2014)
Sudden cardiac death (SCD) is an important cause of mortality worldwide. Although SCD is most often associated with coronary heart disease, the risk of SCD in patients without ischemic heart disease is well-established. Nonischemic cardiomyopathies, including idiopathic dilated cardiomyopathy, hypertrophic cardiomyopathy and arrhythmogenic right ventricular cardiomyopathy represent three unique disease entities that have been shown to be highly associated with SCD and ventricular arrhythmias. A variety of risk stratification tools have been investigated, although the optimal strategy remains unknown. Identification of the arrhythmogenic substrate and treatment of ventricular arrhythmias in these subgroups can be challenging. Herein, we aim to discuss the current understanding of the anatomic and electrophysiologic substrate underlying ventricular arrhythmias and highlight features that may be associated with a higher risk of SCD in these 3 conditions.